"Because your yard is too big": Squatter struggles, the local state and dual power in Uitgenhage, 1985-1986 - Swilling, Mark (My University, 1988)
By focussing largely on the struggle Langa's squatters waged against forced removal, this chapter will attempt to analyse the complex interactions between local township administrators, the white establishment, employers, community organisations and trade unions. To understand this complexity, the romantic conception of unstratified communities united against a monolithinc state needs to be jettisoned. Instead, the internal workings of both the social movements and state apparatuses must be studied. This cannot be achieved, however, without taking into account the impact social movements have on the state and how the actions of state officials affect the strategies of social movements. Furthermore, this relationship does not exist outside the influence employer interests exert on the local state and the way this influence is mediated by trade union pressure. As this chapter will show, once the object of study is extended in this way, social processes come to light that call into question two teleologies. The first is the optimistic view that social movements are only important to the extent that they contribute to the build-up of a national movement that will, at some moment in the future, detonate the collapse of the state. The second is the pessimistic view that social movements only win those concessions that structural conditions allow ruling class interests to concede (1). In both cases, the impact of local movements and how they determine the terms of social organisation is ignored. For the former, the structure of society will only be transformed when the moment of revolution arrives and not before. As far as the latter is concerned, any changes that do take place, occur on terms determined almost entirely by the ruling class.
African Studies Seminar series. Paper presented 14 March, 1988
Keywords: Squatter settlements. South Africa. Uitenhage; Squatters. South Africa. Uitenhage; Uitenhage (South Africa). Race relations; Blacks. Relocation. South Africa; Government, Resistance to. South Africa; Squatter settlements. South Africa